Changes in Czechoslovak Civil Procedure Law in the Interwar Period - Karel Schelle (Journal on European History of Law)
The document highlights the contributions of the 1934 legislation, Law No. 251/1934, in addressing the challenges faced by the Czechoslovak judicial system, particularly focusing on amendments to civil procedure, execution orders, and non-contentious proceedings. It emphasizes the law's objective to alleviate the burden on the Supreme Court and lower courts, outlining specific changes such as the inadmissibility of certain appeals and revisions, the exemption of labor court disputes from these restrictions, and the adjustment of the threshold for petty matters from 300 to 500 Crowns, aiming to streamline judicial processes and reduce court backlogs.